Communication Strategy Pertamina Green CSR Program to Supporting Sustainable Development Goals (SDGs) - Adhianty Nurjanah; Dyah Mutiarin; Erwin Rasyid; Riski Apriliani (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2023)
Pertamina shows the Company's high concern for environmental preservation through the Green Pertamina Program. Therefore, the research formulation focus on examining how the use of media in Pertamina Hijau CSR communication supports sustainable development goals (SDGs)? Approach This research uses a qualitative descriptive approach with content analysis methods on social media Instagram and Website PT. Pertamina in communicating Pertamina Green CSR. Data collection techniques through secondary data obtained from Instagram, websites, and related literature, journals and data sources. The results of this study indicate that Instagram is the most active communication medium to be used in communicating CSR and building awareness of sustainable development goals (SDGs), as well as using the website to support detailed explanations of the Pertamina Hijau CSR program as a form of accountability for program implementation. Pertamina has four empowerment initiatives to support the realization of SDGs in Indonesia, which include Education (Pertamina Smart), Health (Pertamina Sehati), Environment (Pertamina Hijau), and Community Development (Pertamina Berdikari).